Peran Pajak Penghasilan dalam Mengurangi Ketimpangan Sosial dan Ekonomi - Alexander Luis Lung; Darvin Jiong; Jefry Wilson Lius Winardi; William Antonius Salim (Yayasan Literasi Emas Nusantara, 2025)
Social and economic inequality remains a pressing challenge for developing countries, including Indonesia. The disparity in income distribution, access to resources, and economic opportunities reflects a broader systemic issue that impedes inclusive and sustainable growth. This study aims to analyze the role of income tax—particularly progressive income tax—as a fiscal instrument to reduce such inequality. A systematic literature review (SLR) method is employed to synthesize previous research and examine how income tax can function as an effective tool for wealth redistribution. The findings show that when properly managed, income tax revenues can support public services such as education, health, and infrastructure, directly contributing to poverty alleviation and reduced inequality. However, the effectiveness of this approach also depends on administrative capacity, transparency, and the ability to minimize tax avoidance. Therefore, progressive tax policy must be accompanied by institutional reforms and equitable fiscal allocation to ensure long-term impact on social and economic equity.